Laparoskopska holecistektomija zaradi akutnega vnetja žolčnika s kamni pri bolnici z medsebojno obrnjenim položajem notranjih organov - prikaz primera - Černi, Igor (Zdravniški vestnik, 2003)
Background. Situs inversus viscerum totalis (reciprocally reversed position ofinternal organs) is a rare case with genetic predisposition, inherited autosomnously recessive. The presented case involves an older patient with complete transposition of internal organs having acute calculous cholecystitis, which was successfully performed the laparoscopic cholecystectomy. Whilst the production of biliary stones in a case of transposed internal organs is very rare, it may well represent a diagnostic problem. It is not, however, the contraindication for laparoscopic surgery. Patients and methods. The casepresents a 64-year-old patient, whose persistentbiliary colic trouble eventually resulted in acute cholecystitis. Following routine diagnostics, a laparoscopic cholecystectomy was performed and the patient was released in domestic care after three day hospitalization.Conclusions. The laparoscopic cholecystectomy may also be safely performed in a patient with reciprocal transposition of all internal organs, but it is imperative to consider the fact that the extra-hepatic anatomy ofgall bladder and vascular system is the mirror image of normal, right-hand positioned liver.
Keywords: Abdomen; Cholecystectomy, Laparoscopic; Cholecystitis; Cholelithiasis; Holecistitis; Holecistoktemija laparoskopska; infekcije; kirurško zdravljenje; Middle Age; Radiography; Situs Inversus; Situs inverzus; Srednja leta; Surgery; Trebuh; Ultrasonography; Žolčni kamni; žolčnik